Integration of Indigenous Healing Approaches and Western Psychotherapy in Addressing War Trauma Post-Arab Spring - M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Nurzahara Sihombing (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
This study systematically evaluates the effectiveness of integrating indigenous healing approaches with Western psychotherapy in addressing psychological trauma experienced by populations affected by war in the aftermath of the Arab Spring. Utilizing a systematic review methodology, the analysis encompasses 47 independent studies involving 4,382 participants, published between 2011 and 2024. Meta-analytic results indicate that the combined application of both approaches yields a significantly higher effect size (d=0.86, 95% CI [0.72, 1.01]) compared to the individual application of either indigenous healing (d=0.51) or Western psychotherapy (d=0.63). Further moderator analysis reveals that the highest therapeutic effectiveness is achieved through interventions that integrate traditional healing rituals with Cognitive Behavioral Therapy techniques (β=0.41, p<.001) and Eye Movement Desensitization and Reprocessing (β=0.38, p<.001). Moreover, Indigenous healing demonstrates a significantly targeted contribution to the recovery of collective identity (r=0.72, p<.001) and enhancement of social reintegration capacity (r=0.68, p<.001). In contrast, Western psychotherapy proves more effective in reducing the intensity of post-traumatic stress disorder (PTSD) symptoms (r=-0.59, p<.001). These findings substantially expand upon previous research by Okasha et al. (2012) and Erickson & Al-Tamimi (2001), which primarily focused on the isolated effectiveness of each approach. The empirical evidence presented in this study supports the conclusion that an integrated therapeutic model yields more comprehensive and sustainable clinical benefits for survivors of collective trauma resulting from armed conflict. Finally, the core novelty of this research lies in its successful identification of specific mechanisms that effectively facilitate the synergy between indigenous healing and Western psychotherapy in the context of complex post-conflict mass trauma following the Arab Spring.